2020
DOI: 10.1111/bju.15199
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted kidney transplantation: update from the European Robotic Urology Section (ERUS) series

Abstract: Objective To report the results of the robot‐assisted kidney transplantation (RAKT) experience performed in 10 European centres by members of the European Robotic Urology Section (ERUS)‐RAKT group. Patients and Methods This is a multicentre prospective observational study of RAKT. Descriptive analysis of recipients and donor characteristics, surgical data, intraoperative outcomes, complications rate and functional results were collected and analysed. Results Between July 2015 and September 2019, 291 living‐don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 27 publications
7
30
0
Order By: Relevance
“…Although RAKT is still being performed only at selected referral Centers worldwide, current evidence confirms is feasibility, safety and reproducibility (1,2,19,20). In fact, RAKT with regional hypothermia in the setting of "elective" living donation has been shown to achieve favorable short-and mid-term perioperative and functional outcomes (mirroring the principles of open KT) while providing the key advantages of minimallyinvasive surgery (2,3,6,8,(19)(20)(21)(22)(23). Moreover, recent studies demonstrated that RAKT can be safely performed by experienced robotic surgeons even in case of grafts with vascular anomalies (5) or complex recipients such as those with ADPKD (16) or morbid obesity (7,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Although RAKT is still being performed only at selected referral Centers worldwide, current evidence confirms is feasibility, safety and reproducibility (1,2,19,20). In fact, RAKT with regional hypothermia in the setting of "elective" living donation has been shown to achieve favorable short-and mid-term perioperative and functional outcomes (mirroring the principles of open KT) while providing the key advantages of minimallyinvasive surgery (2,3,6,8,(19)(20)(21)(22)(23). Moreover, recent studies demonstrated that RAKT can be safely performed by experienced robotic surgeons even in case of grafts with vascular anomalies (5) or complex recipients such as those with ADPKD (16) or morbid obesity (7,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years minimally invasive operative techniques such as robot-assisted kidney transplantation (RAKT) has been successfully introduced in both living and deceased donor transplants ( 27 32 ). In one of these studies ( 29 ), a comparison of single ( N = 127) vs. multiple ( N = 21) vessel living-donor RAKT was performed in which the vascular reconstruction techniques performed on the back table were similar to ours reported here.…”
Section: Discussionmentioning
confidence: 99%
“…In the years since, RAKT has become an increasingly common procedure in selected high-volume centers. This can be attributed to promising results which have indicated RAKT to be a safe, feasible and reproducible procedure with a potentially improved morbidity as compared to open kidney transplantation (OKT) (16,17).…”
Section: Current Evidencementioning
confidence: 99%
“…Warm ischemia time has already been shown to be a negative predictive factor of long-term patient and graft survival outcomes (35). In the adult RAKT series, a wide range of ischemia times has been described, but no correlation has been found between rewarming time and graft function (16,17). To reduce potential damage after prolonged warm ischemia times, Menon et al have reported a new technique for regional hypothermia with ice slush during vascular anastomosis (15).…”
Section: Specifics Requiring Special Attention In Pediatric Raktmentioning
confidence: 99%